Pengembangan Permainan Berbasis Virtual-Rehability Bagi Pasien Pasca Stroke Menggunakan Myoâ„¢ Armband Device - Ade Suluh Novriananda; Muhammad Aminul Akbar; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Stroke disease is second that cause of death in the world by WHO in 2015. In order to reduce impact of stroke disease, an effort like post-stroke rehabilitation is important. The phase of rehabilitation is a subtantial whereas patients get psychological and educational approach that help patients growth recovery. Patiens perform post-stroke rehabilitation with repeated activities, while patients can be done easily in normal state condition. In this way, patients tend to feel bored because it doesn't feel interesting and fun. In this research, was done the game development using myo armband device that used in the hands of post-stroke patients to train the muscle and nerve of their hands. Myo will detect hand gestures by patients as a game controller. The result of fun testing through questionnaire fulfillment and calculated by the interpretation of index with Likert scale in this research, stated that there are 80% on fun and addictive elements in the game, 76% of all games presented, 72% for instructions on how to play and display games, and 64% for the difficulty level of the game. While on the test score, 3 out of 5 patients experienced a very significant increase seen from how quickly patients complete the game.